Formation of teachers in Brazil: Courses and graduates - Mônica Cerbella Freire Mandarino; Kaizô Iwakami Beltrão (Arizona State University, 2018)
The present article deals with the initial formation of teachers in Brazil from 2000 to 2015. Using data from the census of Higher Education for these 15 years, we analyzed the supply of courses and the volume of enrollments and graduates of teacher certification programs, prolonging the extensive study on teacher education coordinated by Gatti. In addition to this survey, we present an analysis of the socioeconomic profile of the graduates of teacher certification programs, with data from the Enade student questionnaire. This analysis is based on the construction of two variables (factors) using statistical techniques of Optimal Scaling of Ordinal Variables and Factor Analysis. The results show that graduates of teacher certification programs are among those economically disadvantaged and among those who work during the higher education course. It is also shown that most of the graduates, even in 2014, already worked in the area of Education, which may be an effect of the requirement of a higher level for teaching.